Risk of Spouse HIV Status and Anal Sex on HIV/AIDS Transmission in Men Who Have Sex with Men (MSM) at Kendari City Hospital - Sijid, Rahmawati; Jayadipraja, Erwin Azizi; Appe, Samsu; Fadmi, Fitri Rachmillah; Ayi Sukma, Komang (Universitas Ahmad Dahlan, 2025)
Background : The incidence of HIV/AIDS occurs in many productive ages with the highest percentage in men. At Kendari City Hospital, there is a significant increase in new cases of HIV/AIDS every year, especially in the MSM group. The average proportion of HIV/AIDS cases in MSM in 2021 is 65.4%; in 2022 it is 74.3%, and in 2023 it is 77.1%. This study aims to analyse the risk of HIV status and anal sex on HIV/AIDS transmission in the group of men who have sex with men (MSM) at Kendari City Hospital. Method : This type of research is a quantitative study with a case control design. The study population consisted of 349 cases and 423 controls. The minimum sample size taken was 75 case subjects and 75 control subjects, with sample withdrawal using random sampling. Data analysis was carried out descriptively, epidemiology and logistic regression analysis. Results: This research found the Odds Ratio (OR) of HIV status of couples was obtained at 30.545 and anal sex was 7.042. Conclusion : The conclusion in this study is that the HIV status of the couple and anal sex are behavioural factors for the risk of HIV/AIDS in the group of Men who have sex with men at Kendari City Hospital. It is expected that the Kendari City Health Office will increase socialization activities about the use of condoms and examination for sexually transmitted infections as an effort to prevent HIV/AIDS, especially to the MSM group. This can be done through cross-sectoral cooperation with other agencies as well as the involvement of NGOs and moving with the community.